INTERNAL AND MACROECONOMIC FACTORS DETERMINING PROFITABILITY IN COMMERCIAL BANKS: EVIDENCE FROM TURKISH BANKING SECTOR (Third Sector Social Economic Review, 2024)
Banks, which have to work on the basis of profitability and efficiency like other commercial enterprises, need to work on the basis of profitability and efficiency in order to achieve their goals, along with internal factors such as sector shares, distribution of assets and liabilities, interest and non-interest income and expenses, macroeconomic factors such as inflation rate, central bank interest policies, tax policies, gross domestic product and exchange rate policy are also effective.  The aim of this research is to reveal the internal and macroeconomic factors that determine profitability in commercial banks together and with their relative importance. Commercial banks operating in Turkey in the 2014-2024 period and ranking in the top 15 in terms of asset size were included in the research, and quarterly periods from the beginning of 2014 to the beginning of 2024 were taken into account in the financial data and macroeconomic data of the banks. In the research conducted with the panel data analysis method, estimation were made using the Driscoll-Kraay method, which is one of the estimators that can produce robust standard errors. As a result of the research; it was understood that capital adequacy ratio (CAR), loans to total assets ratio (LR), fixed assets to total assets ratio (FIX), interest income ratio (IIR), non-interest income to non-interest expenses coverage ratio (ER), liquid assets to total assets ratio (LAR), asset size (AS) and inflation rate (INF) positively affect return on assets ratio (ROA) and return on equity ratio (ROE), while non-performing loans to total loans ratio (NPL) and interest rate (INT) negatively affect. It was found that equities to total assets ratio (CAP) positively affects return on assets ratio, while deposits to total assets ratio (DR) negatively affects it.
Keywords: Profitability; commercial bank